EMPOWERING RURAL EDUCATORS THROUGH AI LITERACY: CHATGPT TRAINING AT SD NEGERI 3 SIBETAN KARANGASEM BALI - Hamdikatama, Bimantyoso; Kusrini, Kusrini; Utami, Ema (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2025)
The advancement of Artificial Intelligence (AI) has had a significant impact on various sectors, including education. However, the adoption of AI in Indonesia remains uneven, particularly in remote and rural areas. This study aims to assess the effectiveness of a training program on the use of ChatGPT as a teaching aid for elementary school teachers at SD Negeri 3 Sibetan, Karangasem, Bali. The training was designed to enhance teachers' understanding, practical skills, and perceptions of AI integration in education. Using a quantitative approach with a one-group pretest-posttest experimental design, data were collected through conceptual knowledge tests, practical skill observations, and perception questionnaires. The results revealed a significant increase in teachers' knowledge, with average posttest scores rising from 32.2 to 78.0. Additionally, practical skills improved notably, as indicated by a posttest average score of 73.0. Positive perception also increased, with 71% of participants expressing enthusiasm for using ChatGPT in the classroom. Despite limited infrastructure, the training successfully introduced AI-based tools to rural educators, demonstrating the transformative potential of AI in promoting equitable, innovative, and interactive education. This study contributes to the discourse on AI in education and underscores the importance of contextualised teacher training in rural settings.